Descriptions and new records in longhorned beetles (Coleoptera: Cerambycidae) from Central America - Nearns, Eugenio H.; Swift, Ian P. (Zootaxa, 2022)
Two new species of longhorned beetles (Coleoptera: Cerambycidae) from Central America are described and illustrated: Crossomeles copei sp. nov. and Crossomeles oscarcastilloi sp. nov. (Cerambycinae: Rhinotragini) from Mexico and Costa Rica, respectively. A key to the known species of Crossomeles Chemsak & Noguera, 1993 is provided. Also, two new country records are reported: Crossomeles acutipennis Chemsak & Noguera, 1993 from Panama; and Oncideres fisheri Dillon & Dillon, 1946 (Lamiinae: Onciderini) from the United States of America.